Сравнение результатов гамма-активационного анализа и инструментального нейтронного активационного анализа геологических образцов - Алексанян, А. Ю.; Амирханян, С. М.; Аперян, А. Ж.; Гулканян, Г. Р.; Котанджян, Т. В.; Левонян, М. А.; Погосов, В. С.; Погосян, Л. А.; Сааков, А. С.; Шагинян, А. А.
For the first time in Armenia, gamma activation analysis of geological samples of obsidian was carried out using beams of bremsstrahlung photons at the linear electron accelerator of the National Scientific Laboratory after Alikhanyan. It is shown that the results of the chemical composition of the obsidian sample are comparable with the results of instrumental neutron activation analysis (INAA) of the same sample, carried out at the Curt- Engelhom-Center for Archaeometry (Mannheim, Germany), after irradiation with neutrons in a specialized nuclear reactor TRIGA at the Institute of Nuclear Chemistry of the University Mainz. It is also shown that gamma activation analysis makes it possible to determine the content of a number of elements for which the use of INAA is impossible or difficult. На линейном ускорителе электронов Национальной научной лаборатории им. Алиханяна впервые в Армении осуществлен гамма-активационный анализ геологических образцов обсидиана с использованием пучков тормозных фотонов. Показано, что результаты анализа по определению содержания ряда химических элементов в образце обсидиана сопоставимы с результатами инструментального нейтронного активационного анализа (ИНАА) того же образца, проведенного в Центре Ареометрии Майнхайма, Германия, после облучения нейтронами в специализированном ядерном реакторе TRIGA в Институте ядерной химии Университета Майнца. Показано также, что гамма-активационный анализ позволяет определить содержание ряда элементов, для которых применение ИНАА невозможно или затруднено.
Keywords: Физика